Non-alcoholic Fatty Liver Disease and Alcohol-Related Liver Disease: Two Intertwined Entities - Idalsoaga, Francisco; Kulkarni, Anand V.; Mousa, Omar Y.; Arrese, Marco; Arab, Juan Pablo (Frontiers in Medicine, 2020)
Non-alcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease worldwide, with a prevalence of 25–30%. Since its first description in 1980, NAFLD has been conceived as a different entity from alcohol-related fatty liver disease (ALD), despite that, both diseases have an overlap in the pathophysiology, share genetic–epigenetic factors, and frequently coexist. Both entities are characterized by a broad spectrum of histological features ranging from isolated steatosis to steatohepatitis and cirrhosis. Distinction between NAFLD and ALD is based on the amount of consumed alcohol, which has been arbitrarily established. In this context, a proposal of positive criteria for NAFLD diagnosis not considering exclusion of alcohol consumption as a prerequisite criterion for diagnosis had emerged, recognizing the possibility of a dual etiology of fatty liver in some individuals. The impact of moderate alcohol use on the severity of NAFLD is ill-defined. Some studies suggest protective effects in moderate doses, but current evidence shows that there is no safe threshold for alcohol consumption for NAFLD. In fact, given the synergistic effect between alcohol consumption, obesity, and metabolic dysfunction, it is likely that alcohol use serves as a significant risk factor for the progression of liver disease in NAFLD and metabolic syndrome. This also affects the incidence of hepatocellular carcinoma. In this review, we summarize the overlapping pathophysiology of NAFLD and ALD, the current data on alcohol consumption in patients with NAFLD, and the effects of metabolic dysfunction and overweight in ALD.